Gender : Theoretische Paradigmen und queer-feministische Perspektiven - Hettmann, Sandra (Universität Rostock, 2017)
This paper examines the major theoretical paradigms and inherent challenges of gender terminologies on the horizon of Romance/Hispanic Literary and Cultural Studies. Reflecting on the emergence of gender theory in order to observe and question current developments in theoretical approaches, shifts and consequences, the paper provides queer-feminist perspectives from a materialist point of view. By reconsidering the role of existing power structures and the persistence of a fundamental androcentrism, the paper states the need to change analytic strategies and thought patterns regarding gender, and in particular masculinity. Moreover, it demands neither to deny the own embroilment in knowledge production nor to neglect gender relations within dominant culture.
Keywords: Androzentrismus; Geschlechterverhältnis; Feminismus; 100 Philosophie und Psychologie; Androcentrism; Gender relations; Literary and Cultural Studies; Materialist Queer-Feminism; Reflection of Gender Theory